The Effect of Institutional Ownership and Characteristics of The Audit Committee on Corporate Risk Disclosure of Banks In Indonesia - Wuni Utari; Deva Nailul Faiz; Silvia Rosalina; Bima Cinintya Pratama (Journal of Economics, Social, and Humanities, 2023)
This study aims to prove the effect of institutional ownership, and audit committee characteristics on corporate risk disclosure. The population used in this study is a Banking Company listed on the BEI during 2008-2020. The sampling technique used was purposive sampling and 161 samples were obtained that met the criteria. The analytical method used is multiple regression model. Based on the tested hypothesis, it proves that the institutional ownership and number of audit committee meetings have a positive effect on the corporate risk disclosure, while audit committee size have no effect on the corporate risk disclosure.